Phagolysosomal Survival Enables Non-lytic Hyphal Escape and Ramification Through Lung Epithelium During Aspergillus fumigatus Infection - Seidel, Constanze; Moreno-Velásquez, Sergio D.; Ben-Ghazzi, Nagwa; Gago, Sara; Read, Nick D.; Bowyer, Paul (Frontiers in Microbiology, 2020)
Aspergillus fumigatus is the most important mould pathogen in immunosuppressed patients. Suboptimal clearance of inhaled spores results in the colonisation of the lung airways by invasive hyphae. The first point of contact between A. fumigatus and the host is the lung epithelium. In vitro and ex vivo studies have characterised critical aspects of the interaction of invasive hyphae on the surface of epithelial cells. However, the cellular interplay between internalised A. fumigatus and the lung epithelium remains largely unexplored. Here, we use high-resolution live-cell confocal microscopy, 3D rendered imaging and transmission electron microscopy to define the development of A. fumigatus after lung epithelium internalisation in vitro. Germination, morphology and growth of A. fumigatus were significantly impaired upon internalisation by alveolar (A549) and bronchial (16HBE) lung epithelial cells compared to those growing on the host surface. Internalised spores and germlings were surrounded by the host phagolysosome membrane. Sixty per cent of the phagosomes containing germlings were not acidified at 24 h post infection allowing hyphal development. During escape, the phagolysosomal membrane was not ruptured but likely fused to host plasma membrane allowing hyphal exit from the intact host cell in an non-lytic process. Subsequently, escaping hyphae elongated between or through adjacent epithelial lung cells without penetration of the host cytoplasm. Hyphal tips penetrating new epithelial cells were surrounded by the recipient cell plasma membrane. Altogether, our results suggest cells of lung epithelium survive fungal penetration because the phagolysosomal and plasma membranes are never breached and that conversely, fungal spores survive due to phagosome maturation failure. Consequently, fungal hyphae can grow through the epithelial cell layer without directly damaging the host. These processes likely prevent the activation of downstream immune responses alongside limiting the access of professional phagocytes to the invading fungal hypha. Further research is needed to investigate if these events also occur during penetration of fungi in endothelial cells, fibroblasts and other cell types.